PENGARUH LUAS LAHAN, HARGA JUAL TANDAN BUAH SEGAR, UMUR TANAMAN DAN BIAYA PRODUKSI TERHADAP JUMLAH PRODUKSI DAN DAMPAKNYA PADA PENDAPATAN USAHATANI KELAPA SAWIT (Studi Kasus Desa Suko Awin Jaya Kecamatan Sekernan Kabupaten Muaro Jambi) - Julia Jatmika; Hardiani; Jaya Kusuma Edy (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the socio-economic characteristics of farmers and examine the influence of land area, selling price of Fresh Fruit Bunches (FFB), plant age, and production costs on production volume and its impact on oil palm farming income in Suko Awin Jaya Village, Sekernan District, Muaro Jambi Regency. The analysis methods used include descriptive analysis and quantitative analysis using the Multiple Linear Regression model, complemented by classical assumption tests and hypothesis testing (F-test and t-test). The results showed that simultaneously, all independent variables had a significant effect on production volume with a coefficient of determination (R 2) of 0.836550, meaning these variables explain 84% of the production variation. Partially, land area and production costs have a positive and significant influence on production volume. Conversely, the plant age variable has a negative and significant effect, indicating that older plants tend to have declining productivity. The average income of farmers in the study location reached IDR 12,780,474 per month, indicating that this farming business is financially viable as it is well above the minimum wage standard of Jambi Province.